ORBIT: Effective Issue Queue Soft-Error Vulnerability Mitigation on Simultaneous Multithreaded Architectures Using Operand Readiness-Based Instruction Dispatch - Fu, Xin; Li, Tao; Fortes, José (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2008: Anais do XX International Symposium on Computer Architecture and High Performance Computing, 2008)
With the advance of semiconductor processing technology, soft errors have become an increasing cause of failures of microprocessors fabricated using smaller and more densely integrated transistors with lower threshold voltages and tighter noise margins. With diminishing performance returns on wider issue superscalar processors, the microprocessor design industry has opted for using simultaneous multithreaded (SMT) architectures in commercial processors to exploit thread-level parallelism (TLP). SMT techniques enhance overall system performance but also introduce greater susceptibility to soft errors - concurrently executing multiple threads exposes many program runtime states to soft-error strikes at any given time. The issue queue (IQ) is a key micro architecture structure to exploit instruction-level and thread-level parallelism. On SMT processors, the IQ buffers a large number of instructions from multiple threads and is more susceptible to soft-error strikes. In this paper, we explore the use of operand-readiness-based instruction dispatch (ORBIT) as an effective mechanism to mitigate IQ soft-error vulnerability on SMT processors. We observe that IQ soft-error vulnerability is largely affected by instructions waiting for their source operands. The overall IQ soft-error vulnerability can be effectively reduced by minimizing the number of waiting instructions and their residency cycles in the IQ. We develop six techniques that aim to improve IQ reliability with negligible performance degradation on SMT processors. Moreover, we extend our techniques with prediction methods that can anticipate the readiness of source operands ahead of time. The ORBIT schemes integrated with reliability-awareness and readiness prediction achieve more attractive reliability/performance trade-offs. The best of the proposed schemes (e.g. Predict_DelayACE) reduces IQ vulnerability by 79% with only 1% throughput IPC and 3% harmonic IPC reduction across all studied workloads.